Role of Multimodality Imaging in Transcatheter Aortic Valve Replacement. Issue 4 (4th December 2014) - Ramineni, Rajesh; Almomani, Ahmed; Kumar, Arnav; Ahmad, Masood
<x xml:space="preserve">Abstract</x> The treatment of aortic stenosis (AS) has reached an exciting stage with the introduction of transcatheter aortic valve replacement (TAVR). It is the treatment of choice in patients with severe AS who are considered very high risk for surgical valve replacement. Multimodality imaging (MMI) plays a crucial role in TAVR patient selection, intra‐procedure guidance, and follow‐up. With the ever‐increasing scope for TAVR, a better understanding of MMI is essential to improve outcomes and prevent complications.